THE SOCIAL-PEDAGOGICAL NEED OF PREPARING FUTURE TEACHERS FOR THE PROCESS OF CONTINUOUS SPIRITUAL EDUCATION (Scientific journal of the Fergana State University, 2023)
In this article, opinions on increasing the activity of introducing educational standards based on a new approach to the training of future physical education teachers, on awakening a sense of responsibility for the chosen profession, on the development of various reforms in society are presented.